Efektifitas kombinasi terapi kukusan labu siam dan senam anti stroke terhadap penurunan tekanan darah pada Pasien dengan hipertensi - Nurjannah - Tul'aini; Arneliwati - -; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of the research is  to analize the effectivity of combination labu siam steamer therapy and anti stroke exercises for reduce blood pressure to patiens hypertension. The research used quasy experiment design with non-equivalent control group which divided into experimental group and control group. Sample of this research is 30 people divided into 19 people as the experimental group and 19 people as a control group. Sample in this research taken using purposive sampling of techniques sampling which selected based on inclusion criteria. The equipment was used to measure blood pressure is sphygmomanometer. The experimental group were given interventions with combination labu siam steamer therapy and anti stroke exercises on every morning in three days. Data  analysis applied were univariate and bivariate using dependent sample t test and independent sample t test. The result of the reearch showed that mean of the average systolic and diastolic blood pressure before given combination labu siam steamer therapy and anti stroke exercises was 151.23 mmHg and 94.74 mmHg. While mean of the average systolic and diastolic blood pressure after a given combination labu siam steamer therapy and anti stroke exercises of 143.16 mmHg and 89.82 mmHg were mean blood pressure decreased significantly after intervention given by p value  0,000 (<0,05). The conclusion of combination labu siam steamer therapy and anti stroke exercises can reduce blood pressure for patients hypertension. Keywords: anti stroke exercises, hypertension, labu siam.